PROFESIONALISME SEKRETARIS DALAM MENDUKUNG EFEKTIVITAS MANAJEMEN KORESPONDENSI DAN KOMUNIKASI TELEPON BISNIS - Silfi Oktariyani (SECAD, 2025)
The main problem in this research is how much influence leadership and work discipline have on teacher performance at SDN Mekarwangi 04 Bekasi School, both simultaneously and partially. The author's aim in conducting this research is to determine and analyze school culture, leadership and teacher performance as well as the magnitude of the influence of leadership and work discipline on teacher performance at SDN Mekarwangi 04 Bekasi School, both simultaneously and partially. The method used in this research is a descriptive and verification approach. The population in this study were teachers at SDN Mekarwangi 04 Bekasi School with a sample of 30 people. The data in this research is primary data, where the data is obtained from respondents' answers to the questionnaire that the author distributed. As a result of the data analysis that the author has carried out, the results show that there is an influence of Leadership and Work Discipline on the performance of Teachers at the Mekarwangi 04 Bekasi SDN School, both partially and simultaneously. Leadership and Work Discipline have a significant influence simultaneously and partially on teacher performance.